2011
DOI: 10.1002/mrc.2802
|View full text |Cite
|
Sign up to set email alerts
|

Solvent sensitivity of ortho substituent effect on 13C NMR chemical shift of the carboxyl carbon (δco) in benzoic acid

Abstract: A reverse ortho effect is observed for the (13)C NMR chemical shifts of the carboxyl carbon (δ(co)) in benzoic acids measured in aprotic solvents of varying polarity. The ortho effect on δ(co) is best described by a combination of the reverse field and steric accelerating effects of the substituent in an 80: 20 pattern in apolar aprotic solvents and a 60: 40 pattern in dipolar aprotic ones. Interestingly, no good enough correlation was found between δ(co) and log k(1) of the acids measured in similar solvents.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…ortho -Positions show a more complex behavior than the meta and para analogs due to the proximity of the substituent. 17 19 For example, the nitro group causes an increased shielding of ortho -carbons instead of the expected de-shielding similar to that taking place at the para position. 1 , 11 …”
mentioning
confidence: 99%
“…ortho -Positions show a more complex behavior than the meta and para analogs due to the proximity of the substituent. 17 19 For example, the nitro group causes an increased shielding of ortho -carbons instead of the expected de-shielding similar to that taking place at the para position. 1 , 11 …”
mentioning
confidence: 99%
“…The results of solvent effects on δ co of substituted benzoic acids provide a strong evidence for the through‐space π‐polarization mode of transmission of reverse substituent effects on the carboxyl carbon in benzoic acids. The results also show that an apolar aprotic solvent is a distinct preference over a dipolar aprotic one for investigating intrinsic effects of substituents on 13 C chemical shifts at the side chain or ring carbon centers (δ c ) in benzoic acids and other aromatic molecules . The study has shown, in particular, that the transmission of the anomalous (reverse) effect of an m ‐substituent on δ co in benzoic acid molecule can be successfully interpreted by a 5.5:−2.5:1 combination of the localized, extended, and resonance‐induced π‐polarization mechanisms …”
Section: C Nuclear Magnetic Resonance Chemical Shift Of the Carbonymentioning
confidence: 71%
“…The study has demonstrated further that the electronic effect of an m ‐substituent in benzoic acid on the chemical shift at more than two‐bond distant atoms is relayed by a combination of several non‐classical modes, through space‐localized (direct) π‐polarization and through bond extension of the combination being governed by the site of the atom in the molecule . For interpreting the transmission of the o ‐substituent effect in benzoic acid on the chemical shift of the carboxyl carbon, an additional classical mode, the steric effect mode, is taken into account . The results of solvent effects on δ co of substituted benzoic acids provide a strong evidence for the through‐space π‐polarization mode of transmission of reverse substituent effects on the carboxyl carbon in benzoic acids.…”
Section: C Nuclear Magnetic Resonance Chemical Shift Of the Carbonymentioning
confidence: 98%
See 2 more Smart Citations